Teamwork as an emancipatory strategy in teacher training - Hernández Faria, Milagros del Valle (2025)
Teamwork is one of the most valued transversal competences in the educational sector and one of the teaching strategies in the initial training of teachers. The objective is to propose guidelines to promote teamwork as an emancipatory strategy in the teacher training of students in the UNE Rafael María Baralt Biology and Chemistry Project. Quantitative methodology, projective type; field design, non-experimental. The sample was census-based, made up of 20 teachers and 45 students. A questionnaire with 5 response alternatives was applied. The results indicated that teachers more frequently use traditional individual and group activities, and moderately consider the emancipatory vision of teamwork for teacher training. In conclusion, although there are some elements of teamwork in teacher training within the PBQ, these are still in development. The lack of knowledge and disinterest in emancipatory strategies limit their full implementation.